Analysis of the starting phase in competitive swimming - Schnabel, U.; Küchler, J. (1998)
INTRODUCTION: The analysis of results of international championchips and Olympic Games in swimming shows the importance of starting phase for the final performance especially on short distances. Often the winner outruns on the first 15 meters, sufficient for the victory. METHODS: A simple mechanical model for the description of the movement of the body`s center of gravity during the different phases of starting forms the basis for our analysis. With the help of this model the influence of mechanical parameters on starting time can be analyzed. Results of simulation calculations show the central role for starting time played by the horizontal component of the take-off velocity of the body`s center of gravity. On the other side, much attention has to be given to achieved velocity in the transition phase to use individual performance resources. In order to monitor and process data of biomechanical parameters for the analysis of starting phase, a measuring station was designed. By means of this station it is possible, during both performance diagnostic investigations and in training to analyse the athlete`S movement. The measuring procedure is based on a combination of video analysis (split times, kinematic data) and dynamometrics (ground reaction forces on the starting block). The test control, the monitoring of data and the calculation and presentation of results are computer based. INVESTIGATIONS: The measuring station is used for performance diagnostic investigations of the German national swimming team. The results are compared with data from national and international competitions (World Cup, European Championship). CONCLUSIONS: A swimmer can only achieve international top performances when the following three components are given: 1. an optimization of take-off (enhancement of the horizontal component of swimming velocity) 2. a decrease in resistance forces during entry into the water 3. an increase in drag efficiency in the transitition phase (dolphin movement, underwater breaststroke